Stakeholder Engagement and Conflicting Discourses in Urban Policy in the Two Rivers Urban Park, Cape Town: An Argumentative Discourse Analysis - Scott, Charlotte (Department of Civil Engineering, 2019)
Public participation has the potential to either enhance urban development outcomes or entrench disagreement and frustration. A major challenge for policy-makers is how to understand and then respond to the narratives, metaphors and arguments contributed by stakeholders. In analysing the public participation process for the Two Rivers Urban Park (TRUP) in Cape Town, this research applies argumentative discourse analysis to capture and analyse multiple dimensions of stakeholder contributions. Arguments, and other linguistic features, were linked to themes distilled from the data. Associating and matching these themes to stakeholder groups identified discourse coalitions. The analysis supports the claim that the development of TRUP involves more than merely a technical discussion. The metaphors, stories and arguments used by participants to discuss the development of TRUP refer to it as an emblematic issue for the development of the city, its history, the history of South Africa and globalisation across the world. The discourse coalitions identified illuminate diverging ideas of how cities ought to respond to the environment, the private sector and residents. Without this knowledge government cannot hope to respond to stakeholders in a manner they will find satisfactory.